2010
DOI: 10.11111/jkana.2010.16.4.466
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence and Job Stress of Clinical Nurses in Local Public Hospitals

Abstract: Purpose: This study was done to identify the relationship between emotional intelligence (EI) and job stress of clinical nurses in small to medium-sized hospitals. Methods: Data were collected from a convenience sample of 152 nurses working in 4 local public hospitals in one district. EI was measured with the scale developed by Law, Wong, & Song (2004), and job stress with the scale by Choi, Kang, & Woo (2006). Data were analyzed with PASW (SPSS) 18.0, using descriptive statistics, t-test, ANOVA, Scheffe' test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
1
4
0
1
Order By: Relevance
“…Several previous studies have demonstrated that emotional intelligence is a factor influencing job stress [12]. Emotional intelligence modulates the level of personal factors, such as hardness and resilience, according to organizational context [13]. Therefore, in this study, it was classified as a moderator.…”
Section: Conceptual Frameworkmentioning
confidence: 97%
See 1 more Smart Citation
“…Several previous studies have demonstrated that emotional intelligence is a factor influencing job stress [12]. Emotional intelligence modulates the level of personal factors, such as hardness and resilience, according to organizational context [13]. Therefore, in this study, it was classified as a moderator.…”
Section: Conceptual Frameworkmentioning
confidence: 97%
“…Finally, 65 studies in which variables related to job stress were only reported in a single study were excluded, as meta-correlations require a minimum of two studies reporting the same variable to compute the pooled effect size. As a result, 154 studies were included in the meta-analysis (Figure 1, [13,). The following four general characteristics were examined: year of publicati country of publication, sample size, and quality rating.…”
Section: Literature Search and Selectionmentioning
confidence: 99%
“…However, it is important to note the link between emotional intelligence and job stress. Lee ( 2010 ) found a negative relationship between emotional intelligence and job stress among 152 nurses from 4 hospitals in Korea. Similarly, Shukla and Srivastava ( 2016 ) found a negative relationship between trait emotional intelligence and job stress among 564 retail employees, which is our fifth hypothesis.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…In contrast, the conclusion of Yin et al (2013) study exhibited a significantly positive EI influence on DA and no effect on SA. In previous research, Johnson and Spector (2007) and Lee (2010) explored that EI is associated with DA in positive relation and negatively with SA. Pervaiz, Ali, and Asif (2019) stated that emotional intelligence is a multidimensional concept and is explored in many ways also managed in many ways by employees (Moesby-Jensen & Nielsen, 2014).…”
Section: Developing Hypothesis H1 and H2mentioning
confidence: 99%